Biodiversity of potentially “lalapan” vegetables in Kampung Adat Naga, Tasikmalaya, Indonesia - Nurlinda Septiani; Diana Hernawati; Rinaldi Rizal Putra (Biosfer: Jurnal Pendidikan Biologi, 2020)
Kampung Naga is a traditional village or ethnic in Tasikmalaya, Indonesia with a wealth of biodiversity. This ethnic group, with local knowledge, always involves natural richness in everyday life (ethnobotany). However, not many know about utilizing potentially lalapan vegetables that are commonly used daily by the indigenous people of Kampung Naga. Therefore, this research aims to describe the diversity of potentially lalapan vegetables in the ethnobotanical study used by the people of Kampung Adat Naga. Therefore, this research aims to describe the diversity of potentially fresh plants in the ethnobotanical study used by the people of Kampung Adat Naga. The ethnobotanical studies covered include plant species, plant organ parts used, habitus, habitat type, and relative frequency of citation (RFC) calculations. This study was conducted by the qualitative-survey method. The data was analyzed by using an exploratory-descriptive approach and analyzed descriptively quantitatively. The results showed 46 species of potentially fresh plants commonly used by local people in Kampung Adat Naga and 22 families. The plant's widely used part is the 56% leaf organ, a much-found habitus of 37% herb. For habitat types, as much as 38% are found in gardens. In contrast, the highest RFC value is possessed by species Cucumis sativus L. of 0.93. The local wisdom pattern owned by the Kampung Naga community about planting "lalapan" is a form of fundamental knowledge. Therefore it is essential to maintain its preservation as a form of local cultural diversity.